ANALISIS PENGARUH MODAL KERJA, PRODUKTIVITAS KERJA DAN HARGA KOMODITI PINANG TERHADAP PENDAPATAN PENGECER PINANG DI DISTRIK TEMINABUAN KABUPATEN SORONG SELATAN PROVINSI PAPUA BARAT DAYA - Krisna Fransina Lermating; Sri Anggasari Makatita; Hendry Jems Yoel Aidore; Franklin D. Paiki (P3M Politeknik Negeri Ambon, 2023)
Areca nut is one of the main commodities that can support the welfare of areca nut retailers in the Teminabuan District, South Sorong Regency, Southwest Papua Province. This shows that not only increasing the productivity of areca nut is sufficient, but efforts are also needed to increase its marketing by making improvements and improvements. Efforts to improve in the marketing field were carried out to increase marketing efficiency for areca nut retailers in Teminabuan District. These goals include increasing income for traders who rely on betel nut business as a way to increase family economic well-being. The aim of the study was to empirically examine the effect of working capital, work productivity and areca commodity prices on the income of areca nut retailers in Teminabuan District, South Sorong Regency, Southwest Papua Province. The samples taken were 36 areca nut retailers. The sampling method used is non-probability sampling with the application of saturated sampling techniques (census). For data analysis, the Multiple Linear Regression Method was used. The results of this study indicate that working capital, work productivity and prices have a simultaneous and significant effect on the income of areca nut retailers in Teminabuan District, South Sorong Regency. Furthermore, partially working capital has a positive and significant effect on the income of areca nut retailers in Teminabuan District, South Sorong Regency. Meanwhile, work productivity and price partially have no significant effect on the income of areca nut retailers in the Teminabuan District, South Sorong Regency, Southwest Papua Province. Keywords: Betel Retailer Income, Multiple Linear Regression, South Sorong Teminabuan